Rhetorical Appeals Across Different Contexts: A Comparative Analysis of Steve Jobs’ Promotional and Motivational Speeches - Jesse Hykel Zachary Zachary; Sri Gustiani; Wirda Ningsih (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2026)
Persuasive communication is a critical determinant of success in contemporary business, yet few studies have examined how a single business leader adapts classical rhetorical appeals across contrasting communicative contexts. This study analyzed the use of persuasive language in two speeches delivered by Steve Jobs: the 2005 Stanford Commencement Address, a motivational speech, and the 2007 iPhone Launch Presentation, a commercial product presentation. Using a qualitative descriptive approach grounded in Aristotle's rhetorical framework, utterances containing ethos, pathos, and logos were identified from publicly available transcripts that were manually cross-checked against the original video recordings, classified using a theory based coding checklist, classified using a theory-based coding checklist, and analyzed following Miles and Huberman's model of data reduction, data display, and conclusion drawing. The findings show that Jobs employed all three appeals in both speeches but shifted his rhetorical emphasis according to audience and purpose. Pathos dominated the Stanford address through vulnerable personal storytelling about adoption, failure, and mortality, whereas logos and ethos dominated the iPhone presentation through competitor comparison, feature-based reasoning, and appeals to Apple's record of innovation. The study concludes that effective business persuasion is context-dependent: speakers calibrate emotional and logical appeals to fit their objectives. The findings could potentially offer practical insights for business communication instruction in vocational higher education. Keywords: business speech; ethos; logos; pathos; persuasive language; rhetorical appeals